Hydrolysis of Cellulose by Soluble Clostridium Thermocellum and Acidothermus Cellulolyticus Cellulases - Phillip, Brumm; Dan, Xie; Larry, Allen; David, A. Mead (Journal of Enzymes, 2018)
The goal of this work was to clone, express, characterize and assemble a set of soluble thermostablecellulases capable of significantly degrading cellulose. We successfully cloned, expressed, and purified eleven Clostridium thermocellum (Cthe) cellulases and eight Acidothermuscellulolyticus(Acel) cellulases. The performance of the nineteen enzymes was evaluated on crystalline (filter paper) and amorphous (PASC) cellulose. Hydrolysis products generated from these two substrates were converted to glucose using beta-glucosidase and the glucose formed was determined enzymatically. Ten of the eleven Cthe enzymes were highly active on amorphous cellulose. The individual enzymes all produced <10% reducing sugar equivalents from filter paper. Combinations of Cthe cellulases gave higher conversions, with the combination of CelE, CelI, CelG, and CelK converting 34% of the crystalline cellulose. All eight Acel cellulases showed endo-cellulase activity and were highly active on PASC. Only Acel_0615 produced more than 10% reducing sugar equivalents from filter paper, and a combination of six Acel cellulases produced 32% conversion. Acel_0617, a GH48 exo-cellulase, and Acel_0619, a GH12 endo-cellulase, synergistically stimulated cellulose degradation by the combination of Cthe cellulases to almost 80%. Addition of both Acel enzymes to the Cthe enzyme mix did not further stimulate hydrolysis. Cthe CelG and CelI stimulated cellulose degradation by the combination of Acel cellulases to 66%.
Keywords: Clostridium thermocellum; cellulase; cellulose; Acidothermuscellulolyticus; biofuels; endocellulase; cellobiohydrolase